2020
DOI: 10.1515/chem-2020-0152
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of chemical composition of some commercially important fishes with an emphasis on various Malaysian diets

Abstract: This study compares the chemical composition of cockle (Anadara granosa) and some commercially important marine (Asian seabass Lates calcarifer, grouper Epinephelus bleekeri, hardtail scad Megalaspis cordyla, longtail tuna Thunnus tonggol and Indian mackerel Rastrelliger kanagurta) and freshwater (sutchi catfish Pangasius hypophthalmus, Nile tilapia Oreochromis niloticus and eel Monopterus albus) fishes in Peninsular Malaysia. The results show that the proximate composition and trace metal content were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The results indicated a difference in the IOP Publishing doi:10.1088/1755-1315/1262/7/072089 5 ash percentage among the studied species without recording significant differences among them. The ash content of fish is affected by several factors, including: diet, species, temperature, season, geographic location, and salinity [26] These results are consistent with [27] who referred that ash content is reduced by freezing as in Mystus seenghala fish at 12°C. These results differed with [28] who recorded high ash content in frozen sabour and gold mullet, the high ash percentage may be attributed to an inverse relationship between the ash percentage and moisture that led to the concentration of salts in the meat [29,30].…”
Section: Ashsupporting
confidence: 85%
“…The results indicated a difference in the IOP Publishing doi:10.1088/1755-1315/1262/7/072089 5 ash percentage among the studied species without recording significant differences among them. The ash content of fish is affected by several factors, including: diet, species, temperature, season, geographic location, and salinity [26] These results are consistent with [27] who referred that ash content is reduced by freezing as in Mystus seenghala fish at 12°C. These results differed with [28] who recorded high ash content in frozen sabour and gold mullet, the high ash percentage may be attributed to an inverse relationship between the ash percentage and moisture that led to the concentration of salts in the meat [29,30].…”
Section: Ashsupporting
confidence: 85%
“…Fish muscle and bones behave as an excellent source of dispensable minerals and about 65% of minerals are stocked in the skeleton, particularly vertebra (Njinkoue et al, 2016). Rahman et al (2020) reported that a number of different factors such as diet, species, environmental variables chiefly temperature, seasons, salinity, geographical location, and so forth are responsible for bringing variations in the mineral concentration of fish and shellfish. Besides this, the content of minerals and trace elements that make up the total ash contents are also known to depend on other factors such as feeding behaviour, migration ecosystem and environment, even thriving in the same habitat (Abdallah, 2007; Palani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous marine fish proteins safeguard against the development of insulin resistance caused by a poor diet (Kaur et al, 2014; Kim et al, 2016; Liaset et al, 2019). However, when it comes to daily fish consumption, freshwater fishes are considered somewhat better than marine fishes in terms of protein supplied, although at the same time marine fish do provide better daily fish fat, minerals and trace metals (Zn, Mn and Cu) compared with freshwater (Rahman et al, 2020). The research carried out on riverine fish like hilsa, T. ilisha depicted that it contained higher protein content than marine hilsa, despite the fact that the fat and salt content in marine hilsa was reported higher (Debnath et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ash content is influenced by several factors, including: diet, type, temperature, season, geographical location and salinity [31]. One year after, Ulleberg [32] showed that the ash content of all Atlantic salmon fish products and fillets ranged from 0.9-1.5%. Alhamadany et al [33] explained in a study to determine and compare the chemical composition and some major minerals as well as the nutritional value of ten species of economically important fish from the Shatt al-Arab River; Leuciscus The averages with different letters within the same column differ significantly from each other at a significant level of (P<0.05) *…”
Section: Ashmentioning
confidence: 99%